Comparison of Unnoticed Glove Perforations during Minimally Invasive versus Open Surgeries: A Systematic Review and Meta-Analysis - Sachit Anand; Zenon Pogorelić; Apoorv Singh; Carlos Martin Llorente Muñoz; Nellai Krishnan; Anjan Kumar Dhua; Prabudh Goel; Minu Bajpai (MDPI AG, 2022)
Objective: Various studies have depicted the incidence of glove perforations during open (OS) and minimally invasive surgeries (MIS). The aim of this meta-analysis was to compare the incidence of macroscopic and microscopic glove perforations during MIS and OS. Methods: The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Scientific databases (PubMed, Web of Science, Scopus, and EMBASE) were systematically searched for comparative studies depicting the glove perforation rates during MIS and OS. Risk ratios (RR) were calculated for both the outcomes (dichotomous) and the Mantel-Haenszel method was utilized for the estimation of pooled RR. The methodological quality assessment was performed by two independent investigators using the Downs and Black scale. The main outcomes of the study were the proportion of gloves with gross (macroscopic) perforations and the proportion of gloves with microscopic perforations. Results: Four comparative studies including a total of 1428 gloves (435 from the MIS group) were included. Pooling the data demonstrated no difference in the incidence of macroscopic glove perforations among the MIS and OS groups (RR 0.57, 95% CI 0.21 to 1.54, p = 0.27). On the other hand, the incidence of microscopic perforations was significantly higher in the OS group versus the MIS group (RR 0.72, 95% CI 0.55 to 0.95, p = 0.02). However, all the studies had a moderate risk of bias. Conclusions: When compared to OS, the macroscopic glove perforation rate during MIS showed no significant difference. The incidence of microscopic glove perforations was significantly higher during OS as compared to MIS. However, due to the moderate risk of bias of the available comparative studies, the level of evidence of these studies is limited.